2020
DOI: 10.3390/vaccines8030401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vaccinia Virus Inhibitors and Cellular Functions Necessary for Efficient Viral Replication by Screening Bioactives and FDA-Approved Drugs

Abstract: Four decades after the eradication of smallpox, poxviruses continue to threaten the health of humans and other animals. Vaccinia virus (VACV) was used as the vaccine that successfully eradicated smallpox and is a prototypic member of the poxvirus family. Many cellular pathways play critical roles in productive poxvirus replication. These pathways provide opportunities to expand the arsenal of poxvirus antiviral development by targeting the cellular functions required for efficient poxvirus replication. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 79 publications
2
26
1
Order By: Relevance
“…Our results that STAT3 inhibition reduces VACV replication is somehow discrepant to a previous report that inhibition of STAT3 enhanced the replication of ACAM2000, a VACV strain currently used as a vaccine in mice, and keratinocytes [86]. We have independently confirmed the suppression effects on VACV replication using multiple inhibitors and multiple cell types [57]. We do not fully understand the discrepancy, although it could possibly be explained by different cell types or virus strains used in these studies.…”
Section: Plos Pathogenscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results that STAT3 inhibition reduces VACV replication is somehow discrepant to a previous report that inhibition of STAT3 enhanced the replication of ACAM2000, a VACV strain currently used as a vaccine in mice, and keratinocytes [86]. We have independently confirmed the suppression effects on VACV replication using multiple inhibitors and multiple cell types [57]. We do not fully understand the discrepancy, although it could possibly be explained by different cell types or virus strains used in these studies.…”
Section: Plos Pathogenscontrasting
confidence: 99%
“…Notably, stattic, an inhibitor of STAT3 activation [56], significantly reduced the increase in citrate level in VACV-infected cells but not in uninfected cells (Fig 6C). Chemical inhibition of the STAT3 pathway by stattic resulted in a 177-fold reduction [57]. Stattic treatment did not affect HFF viability at the same concentration ( S10B Fig), suggesting that STAT3 signaling is also required for VACV-induced citrate level increase.…”
Section: Plos Pathogensmentioning
confidence: 94%
“… 54 STAT3 inhibitor has been identified to suppress vaccinia virus replication by screening compound library. 55 These results suggest that STAT3 activation is responsible for the increased OVV replication induced by MEK inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…We have previously shown that Gaussia luciferase secretion is not affected by VACV infection of HeLa cells using a transfected plasmid 43 . We measured the Gaussia luciferase activities in media and cell lysates, respectively, to rule out the possibility that Gaussia luciferase was retained in the A549‐EF1α‐Gluc cells due to VACV infection.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Gaussia luciferase secretion is not affected by VACV infection of HeLa cells using a transfected plasmid. 43 We measured the Gaussia luciferase activities in media and cell lysates, respectively, to rule out the possibility that Gaussia luciferase was retained in the A549-EF1α-Gluc cells due to VACV infection. The results indicated that (i) the vast majority (~99%) of Gaussia luciferase activities were in the media, and (ii) in both the media and the cell lysates, VACV infection led to significantly reduced Gaussia luciferase activities (Figure 2D).…”
Section: Monitor Host Shutoff Rapidly Quantitatively and Consecutivel...mentioning
confidence: 99%